Prevalence of Trypanosome Species in Cattle Near Ruma National Park, Lambwe Valley, Kenya: An Update From the Historical Focus for African Trypanosomosis - Kalayou, Shewit; Okal, Michael Nyang'anga; Odhiambo, Peter Otieno; Mathenge, Kawira; Gamba, Daniel Ochieng; Kariuki, Edward; McOdimba, Francis; Masiga, Daniel (Frontiers in Veterinary Science, 2021)
Abstract The effective control of diseases in areas shared with wildlife depends on the validity of the epidemiologic parameters that guide interventions. Epidemiologic data on animal trypanosomosis in Lambwe valley are decades old, and the recent suspected outbreaks of the disease in the valley necessitate the urgent bridging of this data gap. This cross-sectional study estimated the prevalence of bovine trypanosomosis, identified risk factors, and investigated the occurrence of species with zoonotic potential in Lambwe valley. The area is approximately 324 km2, of which 120 km2 is the Ruma National Park. Blood was sampled from the jugular and marginal ear veins of 952 zebu cattle between December 2018 and February 2019 and tested for trypanosomes using the Buffy Coat Technique (BCT) and PCR-High-Resolution Melting (HRM) analysis of the 18S RNA locus. Risk factors for the disease were determined using Logistic regression. The overall trypanosome prevalence was 11.0% by BCT (95% Confidence Interval (CI): 9.0-13.0) and 27.9 % by PCR-HRM (95% CI: 25.1- 30.8). With PCR-HRM as a reference, four species of trypanosomes were detected at prevalences of 12.7 % for T. congolense savannah (95% CI: 10.6-14.8), 7.7% for T. brucei brucei (CI: 6.0-9.4), 8.7% for T. vivax (CI: 6.9-10.5), and 1.3% for T. theileri (CI: 0.6-2.0). About 2.4% of cattle had mixed infections (CI: 1.4-3.41). No human-infective trypanosomes were found. Infections clustered across villages but were not associated with animal age, sex, herd size, and distance from the park. Approximately 85% of infections occurred within 2 km of the park. These findings add to evidence that previous interventions eliminated human trypanosomosis but not bovine trypanosomosis. Risk-tailored intervention within 2 km of Ruma Park, especially in the north and south ends, coupled with stringent screening with molecular tools, could significantly reduce bovine trypanosomosis.